Trzy średniowieczne świadectwa święceń duchownych z diecezji płockiej - Kaczmarek, Krzysztof (Saeculum Christianum. Pismo Historyczne, 2019)
In the Płock Diocesan Archive, it was possible to find unknown testimonies of holy orders from the diocese of Płock from 1486 and 1504. They refer to the ordination of three clerics from Wilkanów and Nowa Wieś by the Płock ordinaries and suffragans. The analysis of these materials is important for the prosopographical studies of the Płock diocese’s clergy in the late Middle Ages.